2011
DOI: 10.1002/jor.21473
|View full text |Cite
|
Sign up to set email alerts
|

Lubricin distribution in the torn human anterior cruciate ligament and meniscus

Abstract: The objective of this study was to: (1) determine the distribution of lubricin in the human torn anterior cruciate ligament (ACL) and meniscus; (2) determine the distribution of lubricin in the human intact ACL and meniscus; (3) and identify potential cellular sources of lubricin in these tissues. Ten torn ACLs and six torn menisci were obtained from surgeries; for comparison, 11 intact ACLs and 13 intact menisci were obtained from total knee replacements. Samples were formalin fixed and processed for immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…This was first suggested by Funakoshi and Spector (2010) in a caprine infraspinatus tendon cell culture study, and then later supported by Zhang et al (2011) in an analysis of human ACL and menisci. Zhao et al (2010) demonstrated that repaired canine flexor tendons treated with a lubricin-containing hyaluronic acid compound showed decreased post-operative adhesions, but this was also associated with impaired tendon healing.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This was first suggested by Funakoshi and Spector (2010) in a caprine infraspinatus tendon cell culture study, and then later supported by Zhang et al (2011) in an analysis of human ACL and menisci. Zhao et al (2010) demonstrated that repaired canine flexor tendons treated with a lubricin-containing hyaluronic acid compound showed decreased post-operative adhesions, but this was also associated with impaired tendon healing.…”
Section: Discussionmentioning
confidence: 91%
“…articular cartilage, meniscus, and tendon (Sun et al, 2006;Lee et al, 2008;Funakoshi et al, 2008;Zhang et al, 2011). Lee et al (2008) reported that bovine ACLs and posterior cruciate ligaments (PCLs) stained for lubricin/PRG4 on their surface, as well as between collagen fibre bundles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many articles refer to the fibroblast gene expression of the ligaments in damaged or pathological joints (20,21,23,24). Our study shows the influence of factors present in normal joint fluid on the gene expression in ACL fibroblasts.…”
Section: Discussionmentioning
confidence: 58%
“…Lubricin was also found on the native surfaces of intact ACLs and on torn edges of ACLs. Thus, it may interfere with the integrative healing process needed for ACL repair (21). Both CIF and CIF-like cocktail stimulated aggrecan expression in CLFs but not in DFs (Tables I and II).…”
Section: Discussionmentioning
confidence: 99%